5.7.14 Problems 1301 to 1400

Table 5.589: Solved using series method

#

ODE

Mathematica

Maple

8323

\[ {}y^{\prime \prime }+x^{2} y^{\prime }+2 x y = 10 x^{3}-2 x +5 \]

8557

\[ {}y^{\prime \prime }+y = 0 \]

8558

\[ {}y^{\prime \prime }-9 y = 0 \]

8559

\[ {}y^{\prime \prime }+3 x y^{\prime }+3 y = 0 \]

8560

\[ {}\left (4 x^{2}+1\right ) y^{\prime \prime }-8 y = 0 \]

8561

\[ {}\left (-4 x^{2}+1\right ) y^{\prime \prime }+8 y = 0 \]

8562

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

8563

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+10 x y^{\prime }+20 y = 0 \]

8564

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

8565

\[ {}\left (x^{2}-9\right ) y^{\prime \prime }+3 x y^{\prime }-3 y = 0 \]

8566

\[ {}y^{\prime \prime }+2 x y^{\prime }+5 y = 0 \]

8567

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }+6 x y^{\prime }+4 y = 0 \]

8568

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }-5 x y^{\prime }+3 y = 0 \]

8569

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

8570

\[ {}\left (-4 x^{2}+1\right ) y^{\prime \prime }+6 x y^{\prime }-4 y = 0 \]

8571

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }+3 x y^{\prime }-3 y = 0 \]

8573

\[ {}y^{\prime \prime }+x y^{\prime }+3 y = x^{2} \]

8574

\[ {}y^{\prime \prime }+2 x y^{\prime }+2 y = 0 \]

8575

\[ {}y^{\prime \prime }+3 x y^{\prime }+7 y = 0 \]

8576

\[ {}2 y^{\prime \prime }+9 x y^{\prime }-36 y = 0 \]

8577

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

8578

\[ {}\left (x^{2}+4\right ) y^{\prime \prime }+3 x y^{\prime }-8 y = 0 \]

8579

\[ {}\left (9 x^{2}+1\right ) y^{\prime \prime }-18 y = 0 \]

8580

\[ {}\left (3 x^{2}+1\right ) y^{\prime \prime }+13 x y^{\prime }+7 y = 0 \]

8581

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }+11 x y^{\prime }+9 y = 0 \]

8582

\[ {}y^{\prime \prime }-2 \left (x +3\right ) y^{\prime }-3 y = 0 \]

8583

\[ {}y^{\prime \prime }+\left (x -2\right ) y = 0 \]

8584

\[ {}\left (x^{2}-2 x +2\right ) y^{\prime \prime }-4 \left (x -1\right ) y^{\prime }+6 y = 0 \]

8585

\[ {}2 x \left (1+x \right ) y^{\prime \prime }+3 \left (1+x \right ) y^{\prime }-y = 0 \]

8586

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-1\right ) y = 0 \]

8587

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }-\left (4 x^{2}+1\right ) y = 0 \]

8588

\[ {}4 x y^{\prime \prime }+3 y^{\prime }+3 y = 0 \]

8589

\[ {}2 x^{2} \left (1-x \right ) y^{\prime \prime }-x \left (1+7 x \right ) y^{\prime }+y = 0 \]

8590

\[ {}2 x y^{\prime \prime }+5 \left (1-2 x \right ) y^{\prime }-5 y = 0 \]

8591

\[ {}8 x^{2} y^{\prime \prime }+10 x y^{\prime }-\left (1+x \right ) y = 0 \]

8592

\[ {}2 x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-2 y = 0 \]

8593

\[ {}2 x \left (x +3\right ) y^{\prime \prime }-3 \left (1+x \right ) y^{\prime }+2 y = 0 \]

8594

\[ {}2 x y^{\prime \prime }+\left (-2 x^{2}+1\right ) y^{\prime }-4 x y = 0 \]

8595

\[ {}x \left (4-x \right ) y^{\prime \prime }+\left (2-x \right ) y^{\prime }+4 y = 0 \]

8596

\[ {}3 x^{2} y^{\prime \prime }+x y^{\prime }-\left (1+x \right ) y = 0 \]

8597

\[ {}2 x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+4 y = 0 \]

8598

\[ {}2 x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }-5 y = 0 \]

8599

\[ {}2 x^{2} y^{\prime \prime }-3 x \left (1-x \right ) y^{\prime }+2 y = 0 \]

8600

\[ {}2 x^{2} y^{\prime \prime }+x \left (4 x -1\right ) y^{\prime }+2 \left (3 x -1\right ) y = 0 \]

8601

\[ {}2 x y^{\prime \prime }-\left (2 x^{2}+1\right ) y^{\prime }-x y = 0 \]

8602

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

8603

\[ {}2 x^{2} y^{\prime \prime }-3 x y^{\prime }+2 y = 0 \]

8604

\[ {}9 x^{2} y^{\prime \prime }+2 y = 0 \]

8605

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }-2 y = 0 \]

8616

\[ {}x^{2} y^{\prime \prime }-x \left (1+x \right ) y^{\prime }+y = 0 \]

8617

\[ {}4 x^{2} y^{\prime \prime }+\left (1-2 x \right ) y = 0 \]

8618

\[ {}x^{2} y^{\prime \prime }+x \left (x -3\right ) y^{\prime }+4 y = 0 \]

8619

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (4 x^{2}+1\right ) y = 0 \]

8620

\[ {}x \left (1+x \right ) y^{\prime \prime }+\left (1+5 x \right ) y^{\prime }+3 y = 0 \]

8621

\[ {}x^{2} y^{\prime \prime }-x \left (1+3 x \right ) y^{\prime }+\left (1-6 x \right ) y = 0 \]

8622

\[ {}x^{2} y^{\prime \prime }+x \left (x -1\right ) y^{\prime }+\left (1-x \right ) y = 0 \]

8623

\[ {}x \left (x -2\right ) y^{\prime \prime }+2 \left (x -1\right ) y^{\prime }-2 y = 0 \]

8624

\[ {}x \left (x -2\right ) y^{\prime \prime }+2 \left (x -1\right ) y^{\prime }-2 y = 0 \]

8625

\[ {}4 \left (x -4\right )^{2} y^{\prime \prime }+\left (x -4\right ) \left (x -8\right ) y^{\prime }+x y = 0 \]

8627

\[ {}x y^{\prime \prime }+y^{\prime }-x y = 0 \]

8628

\[ {}x y^{\prime \prime }+\left (-x^{2}+1\right ) y^{\prime }-x y = 0 \]

8629

\[ {}x^{2} y^{\prime \prime }+x \left (2 x +3\right ) y^{\prime }+\left (1+3 x \right ) y = 0 \]

8630

\[ {}4 x^{2} y^{\prime \prime }+8 x \left (1+x \right ) y^{\prime }+y = 0 \]

8631

\[ {}x^{2} y^{\prime \prime }+3 x \left (1+x \right ) y^{\prime }+\left (1-3 x \right ) y = 0 \]

8632

\[ {}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }-y = 0 \]

8633

\[ {}x^{2} y^{\prime \prime }+2 x \left (x -2\right ) y^{\prime }+2 \left (2-3 x \right ) y = 0 \]

8634

\[ {}x^{2} \left (2 x +1\right ) y^{\prime \prime }+2 x \left (6 x +1\right ) y^{\prime }-2 y = 0 \]

8635

\[ {}x^{2} y^{\prime \prime }+x \left (3 x +2\right ) y^{\prime }-2 y = 0 \]

8636

\[ {}x y^{\prime \prime }-\left (x +3\right ) y^{\prime }+2 y = 0 \]

8637

\[ {}x \left (1+x \right ) y^{\prime \prime }+\left (5+x \right ) y^{\prime }-4 y = 0 \]

8638

\[ {}x \left (1+x \right ) y^{\prime \prime }+\left (5+x \right ) y^{\prime }-4 y = 0 \]

8639

\[ {}x^{2} y^{\prime \prime }+x^{2} y^{\prime }-2 y = 0 \]

8640

\[ {}x \left (1-x \right ) y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

8641

\[ {}x \left (1-x \right ) y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

8642

\[ {}x y^{\prime \prime }+\left (3 x +4\right ) y^{\prime }+3 y = 0 \]

8643

\[ {}x y^{\prime \prime }-2 \left (x +2\right ) y^{\prime }+4 y = 0 \]

8644

\[ {}x y^{\prime \prime }+\left (2 x +3\right ) y^{\prime }+4 y = 0 \]

8645

\[ {}x \left (x +3\right ) y^{\prime \prime }-9 y^{\prime }-6 y = 0 \]

8646

\[ {}x \left (1-2 x \right ) y^{\prime \prime }-2 \left (x +2\right ) y^{\prime }+8 y = 0 \]

8647

\[ {}x y^{\prime \prime }+\left (x^{3}-1\right ) y^{\prime }+x^{2} y = 0 \]

8648

\[ {}x^{2} \left (4 x -1\right ) y^{\prime \prime }+x \left (1+5 x \right ) y^{\prime }+3 y = 0 \]

8649

\[ {}x y^{\prime \prime }+y = 0 \]

8650

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+\left (3+4 x \right ) y = 0 \]

8651

\[ {}2 x y^{\prime \prime }+6 y^{\prime }+y = 0 \]

8652

\[ {}4 x^{2} y^{\prime \prime }+2 x \left (2-x \right ) y^{\prime }-\left (1+3 x \right ) y = 0 \]

8653

\[ {}x^{2} y^{\prime \prime }-x \left (6+x \right ) y^{\prime }+10 y = 0 \]

8654

\[ {}x y^{\prime \prime }+\left (2 x +3\right ) y^{\prime }+8 y = 0 \]

8655

\[ {}x \left (1-x \right ) y^{\prime \prime }+2 \left (1-x \right ) y^{\prime }+2 y = 0 \]

8656

\[ {}x \left (1-x \right ) y^{\prime \prime }+2 \left (1-x \right ) y^{\prime }+2 y = 0 \]

8658

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

8659

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+\left (8+5 x \right ) y = 0 \]

8660

\[ {}x y^{\prime \prime }+\left (3-x \right ) y^{\prime }-5 y = 0 \]

8661

\[ {}9 x^{2} y^{\prime \prime }-15 x y^{\prime }+7 \left (1+x \right ) y = 0 \]

8662

\[ {}x^{2} y^{\prime \prime }+x \left (1-2 x \right ) y^{\prime }-\left (1+x \right ) y = 0 \]

8663

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (x^{3}+x +1\right ) y = 0 \]

8664

\[ {}2 x \left (1-x \right ) y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

8665

\[ {}x y^{\prime \prime }+y^{\prime }+x \left (1+x \right ) y = 0 \]

8666

\[ {}x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }-\left (6 x^{2}-3 x +1\right ) y = 0 \]

8667

\[ {}x y^{\prime \prime }+x y^{\prime }+\left (x^{4}+1\right ) y = 0 \]

8668

\[ {}x \left (x -2\right )^{2} y^{\prime \prime }-2 \left (x -2\right ) y^{\prime }+2 y = 0 \]